Ação do LASSBio 294 sobre os parâmetros cardiovasculares em modelo experimental de cardiomiopatia dilatada em coelhos - Costa, Ana Paula Araújo (2016)
Dilated cardiomyopathy (DCM) is a disease of the heart muscle that culminates in dilatation of the left ventricle, or both, and myocardial contractile dysfunction. The clinical phase of the disease is characterized by congestive heart failure signs (CHF), with or without arrhythmias. The treatment involves the use of drugs aimed at reducing the signs of CHF and arrhythmias, with diuretics, positive inotropic, vasodilator and antiarrhythmic. A new drug candidate (LASSBio 294), capable of promoting combined positive inotropic and vasodilating effects, has recently been developed, and have been tested in pre-clinical study in healthy Beagle dogs with promising results. Therefore, this study proposed to verify the action of the drug prototype LASSBio 294, at a dose of 2mg/Kg on cardiovascular parameters of rabbits with DCM experimentally induced by doxorubicin, using as positive control the pimobendan at a dose of 0.3mg/kg. The DCM was induced by intravenous administration of 1 mg/kg of doxorubicin, at a concentration of 2mg/ml, twice a week, for three weeks, and then weekly until it reached fractional shortening less or equal to 25%. As methods of evaluating the LASSBio 294 action on the cardiovascular system of rabbits and monitor the induction of DMC, the following tests were performed: electrocardiography, echodopplercardiography, measurement of blood pressure, chest radiograph, dosage of cardiac lesions, and kidney and liver function biomarkers and hematologic evaluation. At the end of the induction protocol the animals were randomly divided into two groups A (LASSBio 294) and B (pimobendan) and underwent treatment for 30 days, twice a day. At the end of the study it was concluded that the DCM model induced by doxorubicin is a good model to study the disease and its consequences, leading to systolic and diastolic dysfunction with dilatation of the left ventricle. However the time for induction of DCM is inaccurate and the occurrence of multisystemic toxicity, such as nephrotoxicity and myelosuppression, contributes to high mortality rate in this model (35%). It can be concluded that LASSBio 294 is effective in increasing systolic function, improving diastolic function, without altering rabbits blood pressure, has no pro-arrhythmogenic or toxic effect, and reduced the serum creatinine concentration of the animals, but it does not prevent the evolution of the congestive condition.